(untitled) (Norwood, Mass., 1995)
Contains bibliographic information for all biomedical and health sciences and numbered congresses that are in the National Library of Medicine's collection plus a limited number of titles not held by NLM but indexed in MEDLINE, Biotechseek, or HEALTH.
Keywords: Thuốc,Medicine; Tạp chí định kỳ,Periodicals